Creation and anthropology: N.F.S. Grundtvig as humanist and feminist. Issue 2 (7th April 2021) - Pedersen, Else Marie Wiberg
Abstract: This article focuses on Scandinavian creation theology by way of the anthropology of the Happy Dane, the theologian, author, hymn writer, poet, and pastor Nicolai Frederik Severin Grundtvig (1783–1872). After having given two examples of Grundtvig's and Grundtvigians' encounter with USA in the past, it is demonstrated how the Lutheran Grundtvig, based on his positive and organic creation theology, fought ideas of creational hierarchies, whether slavery or subjection of women. Grundtvig logically and naturally connected his creation theology to a humanist anthropology of which not the devil but God was Creator and sole subject. As in Galatians 3:28, this encompassed a feminist view as he acknowledged two equal sexes and genders: all humans are equal regardless of color of the skin, sex, or belief and hence should have human rights equally.